Development of Natural Material-Based Art-Based Learning Model to Stimulate Aesthetic Experiences in Early Children - Deny Dwi Kartika; Sri Utaminingsih; Nur Fajrie (STKIP Taman Siswa Bima, 2023)
The purpose of this study is to analyze needs, develop designs, and analyze the effectiveness of nature-based art-based learning models for stimulating aesthetic experiences in early childhood in Kindergarten, Banjarsari District, Surakarta City. This research is a type of R&D research and development. The results of the study: 1) teachers and students need a learning model based on natural materials with an art approach so that they can stimulate children's aesthetic experiences. Learning models that can be implemented easily and do not require a lot of money by utilizing nature and the surrounding environment; 2) the design of art-based learning models based on natural materials includes learning natural-based painting, learning natural-based collage art, learning natural-based handicraft art, learning natural-based batik art, learning natural-based color art; 3) the art-based learning model based on natural materials is effective in stimulating children's aesthetic experience. In this case, the value of developing an art-based learning model based on natural materials is effective in stimulating children's aesthetic experience.